Pengaruh Bauran Pemasaran dan Layanan Purna Jual terhadap Nilai Pelanggan serta implikasinya pada Kepuasan Pelanggan - Dudung Juhana (Kontigensi : Jurnal Ilmiah Manajemen, 2014)
The current phenomenon shows that despite the growth of market share increase, but if it is not accompanied by the ability to deliver value to the customer, then the customer will in turn be abandoned. Thus it becomes an important thing for a company to perform activities of creation and adding value to the customer explained. Therefore the competition that occurs is essentially strives to create superior customer value. With regard to customer value Philip Kotler and Gary Armstrong (2008: 24) states, that by creating superior customer value, the company creates highly satisfied customers and remain loyal and want to buy again. The phenomenon that shows the problems of customer satisfaction Honda brand vehicles appear from the market share, which tends to decrease, as explained above. Based on these explanations, the formulation of the problem is; (1) How is the marketing mix, after-sales service, customer value, and customer satisfaction motorcycles Honda brand in Bandung, (2) How is the relationship between the marketing mix with after-sales service of two-wheel motor vehicles Honda brand in Bandung. (3) the extent of the marketing mix and sales services affect the customer value of two-wheel motor vehicles Honda brand in Bandung, (4) the extent of customer value effect on customer satisfaction motorcycles Honda brand in Bandung. In accordance with the nature of research is descriptive and verification, in this study used methods of descriptive survey and explanatory survey. The unit of analysis of this research is the level of the individual, namely the two-wheeled motor vehicle production Honda brand in 2009 in Bandung. Observations using time horizon with cross section data. Descriptive analysis of the research data can be used to enrich the discussion, and to describe the condition variable being studied.In the analysis of verification will be testing the hypothesis using structural equation modeling. Based on the research that has been done on the effect of the marketing mix performance and the performance of after-sales service to the customer value as well as its implications on customer satisfaction motorcycles of Honda production in 2009 in Bandung, conducted on 381 customers. A number of conclusions as follows: Performance marketing mix motorcycles of Honda production in 2009 in the city as a whole has done well, performance marketing mix motorcycles of Honda production in 2009 in the city as a whole has done well , performance marketing mix and the performance of after-sales services simultaneously affect the value of customers motorcycles of Honda production in 2009 in the city of Bandung, performance marketing mix affect the value of customers motorcycles of Honda production in 2009 in Bandung, performance service sales affect the value of customers motorcycles of Honda production in 2009 in the city of Bandung, customer value effect on customer satisfaction motorcycle brand Honda year 2009 production in Bandung.